Design of water level controller using fuzzy logic technique for water tank system: article / Mohamad Safrul Hadi Mohamad Isa - Mohamad Isa, Mohamad Safrul Hadi (2007)
The measurement of liquid level is important in industrial plants. In most of the operations, the ability to conduct accurate level measurement is very crucial since that it can make a difference in making a profit or taking a loss. Therefore, inaccurate level measurement or failure to take measurement can and will cause serious results. This project is to design a valve controller to control the liquid inlet flow in the water level control system. The suitable type of controller has been identified to be using Fuzzy Logic technique, thus the proposed method could be used to solve the inaccurate level of measurement problem. This valve controller uses intelligent feedback control scheme to produce an ideal liquid level for the next process.